Work and women’s well-being: religion and age as moderators - Mohd. Noor, Noraini (Springer, 2008)
Religion has been found to moderate the stress–strain relationship. This moderator role, however, may be dependent on age. The present study tested for the threeway interaction between work experience, age, and religiosity in the prediction of women’s well-being, and predicted that work experience and religiosity will combine additively in older women, while in younger women religiosity is predicted to moderate the relationship between work experience and well-being. In a sample of 389 married Malay Muslim women, results of the regression analyses showed significant three-way interactions between work experience, age, and religiosity in the prediction of well-being (measured by distress symptoms and life satisfaction). While in younger women the results were in line with the predictions made, in the older women, both additive and moderator effects of religiosity were observed, depending on the well-being measures used. These results are discussed in relation to the literature on work and family, with specific reference to women’s age, religion, as well as the issue of stress–strain specificity.